A cloud based framework for e-government implementation in developing countries - Al-Maatouk, Qusay; Bin Othman, Mohd Shahizan; Rana, Muhammad Ehsan; Al-Rahmi, Waleed Mugahed (International Journal of Engineering and Technology, 2018)
Cloud Computing technology is achieving a significant cost saving, business agility, and high scalability. However, it is a relatively new technology and its successful implementation in the governmental organizations needs careful consideration due to data sensitivity. Success-ful adoption of cloud-based solutions is the key for realizing the expected benefits of cloud computing technologies in the public agencies. The aim of this research is to develop a strategic framework to adopt cloud-based solutions in the public sector to improve e-government processes in developing countries. The purpose of the developed framework is to reduce the time and cost of the processes that contain interaction among governmental agencies and citizens through adopting cloud-based solutions. The framework was formulated based on the collected data analysis and the conclusions from experts’ interviews. This study provides detailed guidelines to a successful launch and implementation of cloud-based solutions for e-government initiatives in the public sector.